1993
DOI: 10.1161/01.cir.88.1.250
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous epicardial and endocardial activation sequence mapping in the isolated canine right atrium.

Abstract: The findings of this study demonstrate that epicardial and endocardial activation can be discordant in specific regions and that discordance increases with abnormal activation sequences. Many of the differences in the epicardial and endocardial activation can be correlated with the heterogeneity of the anatomic architecture of the right atrium. The study also demonstrates that reentry can occur in a three-dimensional plane using the epicardial and endocardial surfaces connected by transmural muscle fibers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
92
0
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(96 citation statements)
references
References 23 publications
3
92
0
1
Order By: Relevance
“…AF is often described as a disorganized phenomenon, [3][4][5][6][7][8] but recently many features that suggest an underlying order have been reported. 9-11 Slocum et al showed that the power spectrum of AF had a discrete peak in the 4-9 Hz band, 15 and Gerstenfeld et al demonstrated preferential routes of wave propagation during AF by showing transient linking of atrial excitation.…”
Section: Discussionmentioning
confidence: 99%
“…AF is often described as a disorganized phenomenon, [3][4][5][6][7][8] but recently many features that suggest an underlying order have been reported. 9-11 Slocum et al showed that the power spectrum of AF had a discrete peak in the 4-9 Hz band, 15 and Gerstenfeld et al demonstrated preferential routes of wave propagation during AF by showing transient linking of atrial excitation.…”
Section: Discussionmentioning
confidence: 99%
“…24 A single relatively stable source in canine RA using a high concentration of acetylcholine by Schuessler et al, 8 and multifocal AF in the sterile pericarditis model by Waldo and colleagues, 6,25 as well, have been reported. Jalife and colleagues 4,26 used phase-based optical signal processing to demonstrate rotor activities with a spectrum of scenarios from single meandering rotor to multiple, periodic rotors giving rise to fibrillatory activation.…”
Section: Progressive Remodeling Of Atrial Tissue With Af Continuationmentioning
confidence: 99%
“…Localized drivers are difficult to detect in persistent AF with conventional techniques because of sequential temporospatial mapping, lack of specificity of complex atrial electrograms, intermittent firing, and spatial meandering. [7][8][9] Wide-field mapping tools have been used to capture these sources with the use of balloon, multispline probes 5,[10][11][12][13][14] or electrode arrays enveloping the torso. [15][16][17][18] Recent developments have allowed biatrial AF mapping using activation or phase-based analysis of body surface potentials.…”
mentioning
confidence: 99%
“…2,[5][6][7][8][9][10][11][12] Electric dissociation between the endocardial bundle network and the epicardial layer (EED) during AF is a prerequisite condition for transmural conduction of fibrillation waves because only in the presence of EED electric activity in 1 layer of the atrial wall can encounter excitable tissue in the opposing layer.We recently demonstrated that in goats EED increases during the first 6 months of AF, 13 which might well explain the higher incidence of breakthrough in complex substrates for AF. However, increasing evidence for altered intracellular Ca 2+ handling in atrial myocytes of AF patients supports the hypothesis that ectopic focal discharges because of triggered activity might also occur during AF and contribute to its perpetuation.…”
mentioning
confidence: 99%